Exploring the Factors that Influence Students' Willingness to Pursue Entrepreneurship - Mlotshwa, Semukele Hellen; Ebewo, Patrick; Ndlovu, Elona (Magister Manajemen of Universitas Islam Nahdlatul Ulama Jepara, 2024)
Entrepreneurship has emerged as a significant driver of economic growth and innovation worldwide. Understanding the factors influencing students' willingness to pursue entrepreneurship is crucial for fostering entrepreneurial ecosystems and cultivating future leaders. This paper explores the multifaceted influences on students' entrepreneurial intentions by synthesising existing literature and empirical studies. Drawing upon theories such as the Theory of Planned Behaviour, Social Cognitive Theory, and Entrepreneurial Event Theory, this research examines individual, contextual, and environmental factors shaping students' attitudes, subjective norms, and perceived behavioural control towards entrepreneurship. Additionally, it investigates the role of educational experiences, family background, socio-cultural factors, and institutional support in shaping entrepreneurial intentions among students. Through a comprehensive review and analysis, this paper offers insights into the complex interplay of factors influencing students' willingness to engage in entrepreneurial activities, thus providing implications for educational policies, entrepreneurship education programs, and future research directions.